Key Metabolic Enzymes Underlying Astrocytic Upregulation of GABAergic Plasticity - Kaczor, Przemysław T.; Mozrzymas, Jerzy W. (Frontiers in Cellular Neuroscience, 2017)
GABAergic plasticity is recognized as a key mechanism of shaping the activity of the neuronal networks. However, its description is challenging because of numerous neuron-specific mechanisms. In particular, while essential role of glial cells in the excitatory plasticity is well established, their involvement of these cells in regulation of GABAergic plasticity only starts to emerge. To address this problem, we used two models: neuronal cell culture (NC) and astrocyte-neuronal co-culture (ANCC), where we chemically induced long-term potentiation at inhibitory synapses (iLTP). iLTP could be induced both in NC and ANCC but in ANCC its extent was larger. Importantly, this functional iLTP manifestation was accompanied by an increase in gephyrin puncta size. Furthermore, blocking astrocyte Krebs cycle with fluoroacetate in ANCC prevented enhancement of both mIPSC amplitude and gephyrin puncta size but this effect was not observed in NC, indicating a key role in neuron-astrocyte cross-talk. Blockade of monocarboxylate transport with 4CIN abolished iLTP both in NC and ANCC and in the latter model prevented also enlargement of gephyrin puncta. Similarly, blockade of glycogen phosphorylase with BAYU6751 prevented enlargement of gephyrin puncta upon iLTP induction. Finally, block of glutamine synthethase with MSO nearly abolished mIPSC increase in both NMDA stimulated cell groups but did not prevent enlargement of gephyrin puncta. In conclusion, we provide further evidence that GABAergic plasticity is strongly regulated by astrocytes and the underlying mechanisms involve key metabolic enzymes. Considering the strategic role of GABAergic interneurons, the plasticity described here indicates possible mechanism whereby metabolism regulates of the network activity.